Use of a cross-platform messaging technology to strengthen the obstetric referral system in the Greater Accra region, Ghana: findings from a pilot programme. (March 2019) - Owen, Medge; Bryce, Fiona; Tulenko, Samantha; Olufolabi, Adeyemi; Srofenyoh, Emmanuel
Abstract: Background: Ghana's Country Action Plan identified weak obstetric referral systems as a major barrier to achieving the Millennium Development Goals for maternal mortality. High-risk referrals are often delayed, leading to severe patient compromise or death during transport to tertiary hospitals or soon after arrival. Essential components for an effective obstetric referral system include: an adequately resourced referral centre; active collaboration across sectors; formalised communication and transport arrangements; supervision and accountability of performance; the capacity to monitor effectiveness; and policy support. Here, we describe the use of a cross-platform messaging system in a pilot programme to promote the uptake of best obstetric referral practices in remote regions. Methods: We selected 13 institutions in the Greater Accra region of Ghana to host the implementation of interventions that included the establishment of an early warning system for major obstetric complications, the development of prereferral treatment guidelines, and the application of WhatsApp mobile technology to facilitate remote communication. Participants included staff from eight health centres; four district hospitals; the Greater Accra Regional Hospital; doctors, administrators, and representatives from other tertiary hospitals in Accra; and medical consultants abroad. Findings: The Kybele WhatsApp mobile technology platform was launched on March 1, 2017, and by May 31, 2018, 1312 cases have been posted; an average of 88 cases per month. Platform users have grown from 69 at launch to 110 participants by April 30, 2018, including the Ghana national ambulance service. An analysis of 618 responses on the messaging platform between March 1, 2017, and Aug 31, 2017, showed that median response time was 17 mins and 511 cases (83%) had a receiving hospital identified. The most common referral indications were: pre-eclampsia 226 (37%), obstructed labour 151 (24%), preterm labour 148 (24%), fetal compromise 86 (14%), and haemorrhage 62 (10%). In 279 cases (45%), treatment instructions were given over the platform about how to stabilise the patient before transfer. The platform provided feedback on patient outcomes, announced system failures (such as oxygen outages and anaesthesia machine malfunctions), and discussed near-misses as learning opportunities. Interpretation: Uptake on the Kybele WhatsApp platform has been rapid and sustained. Care providers and administrators recognise the potential of the cross-platform messaging system to improve obstetric referral processes and to reduce treatment delay. The platform has highlighted improvements in care at the district and subdistrict hospitals, including better management and stabilisation before patient transfer. Findings from this pilot programme could be used to inform development of similar programmes in other low-resource obstetric referral networks. Funding: USAID Systems for Health, Kybele, and Ghana Health Service.